The stable carbon isotope signature of methane produced by saprotrophic fungi [dataset] - Schroll, Moritz; Keppler, Frank; Greule, Markus; Eckhardt, Christian; Zorn, Holger; Lenhart, Katharina (Universität, 2020)
Fungi have recently been identified to produce the greenhouse gas methane. Here, we investigated the stable carbon isotope values of methane produced by saprotrophic fungi. Our results show that stable isotope values of methane by fungi are dependent on the fungal species and the metabolized substrate. They cover a broad range and overlap with stable carbon isotope values of methane reported for methanogenic archaea, thermogenic degradation of organic matter and other eukaryotes.
Gesehen am 29.06.2020
Keywords: Forschungsdaten; Datenbank